2022
DOI: 10.13057/biodiv/d230444
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, domination and behavior of mosquitoes in filariasis endemic area of Bogor District, West Java, Indonesia

Abstract: Abstract. Nirwan M, Hadi UK, Soviana S, Satrija F, Setiyaningsih S. 2022. Diversity, domination and behavior of mosquitoes in filariasis endemic area of Bogor District, West Java, Indonesia. Biodiversitas 23: 2093-2100. A study on the diversity, dominance and behavior of mosquitoes was done in the two filariasis endemic areas in Bogor District, West Java, Indonesia. The objectives of this study were to determine the diversity, dominance and behavior of mosquitoes and their importance as vectors of filariasis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In that study, Brugia malayi was detected as captured Mansonia annulifera (39). This corresponds to the data provided by the Indonesian Ministry of Health, indicating that Brugia malayi is responsible for 70% of lymphatic filariasis cases in Indonesia (40).…”
Section: Vector Of Lymphatic Filariasissupporting
confidence: 87%
“…In that study, Brugia malayi was detected as captured Mansonia annulifera (39). This corresponds to the data provided by the Indonesian Ministry of Health, indicating that Brugia malayi is responsible for 70% of lymphatic filariasis cases in Indonesia (40).…”
Section: Vector Of Lymphatic Filariasissupporting
confidence: 87%
“…quinquefasciatus was caused by the high population density and habitat conditions that support its developmental stages. Culex quinquefasciatus mosquitoes are considered intelligent vectors because they have the ability to thrive and survive in a wide range of environmental conditions [8].…”
Section: Discussionmentioning
confidence: 99%
“…Anopheles barbirostris is known as a vector of filariasis in the limited area of Eastern Indonesia [8]. Recent studies mention the expansion of the spread of An.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has revealed that Cx. quinquefasciatus predominate in a number of provinces, including Banten, West Java, Lampung, East Java, North Maluku, and Maluku (29), and in many districts, including Tasikmalaya (30), Subang (31), Bogor (32), and Tangerang (33). The major LF vector in Indonesia is Cx.…”
Section: Discussionmentioning
confidence: 99%